Constructing History, Culture and Inequality : The Betsileo in the Extreme Southern Highlands of Madagascar - Evers, Sandra (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
During the early 20th century, a group of ex-slaves established a frontier society in the no-man's-land of the extreme Southern Highlands of Madagascar. First settlers skilfully deployed a fluid set of Malagasy customs to implant a myth of themselves as tompon-tany or "masters of the land". Eventually, they created a land monopoly to reinforce their legitimacy and to exclude later migrants. Some of them were labelled andevo ("slave" or "slave descent"). The tompon-tany prohibited the andevo from owning land, and thereby from having tombs. This book focuses on the plight of the tombless andevo, and how their ascribed impurity and association with infertility, illness, death and misfortune made them an essential part of the tompon-tany world-view.